大動脈内バルーン遮断の予防的使用により脾動脈瘤破裂の緊急開腹止血術中に良好な循環動態を保ち得た1例(A case of a stable hemodynamic condition during urgent laparotomy maintained by prophylactic use of resuscitative endovascular balloon occlusion of the aorta (REBOA) in a patient with ruptured splenic artery aneurysm). Issue 2 (18th February 2021) - (Katsuhiko Hashimoto), 橋本 克彦; (Tokiya Ishida), 石田 時也; (Kazuaki Shinohara), 篠原 一彰
ABSTRACT: We report a case with a ruptured splenic artery aneurysm (SAA) who underwent an urgent laparotomy for hemostasis. During the surgery, we prophylactically used resuscitative endovascular balloon occlusion of the aorta (REBOA) and were able to maintain a stable hemodynamic condition. The patient was a 46–year–old man complaining about left abdominal pain with a history of non–alcoholic steatohepatitis, liver cirrhosis, portal hypertension, and esophageal varices. According to the medical history, physical exams, and findings of abdominal ultrasonography, we thought primarily of intra–abdominal hemorrhage, not variceal rupture. An enhanced CT scan revealed a ruptured SAA. We decided to perform urgent laparotomy to remove the spleen and ruptured SAA. We prophylactically used REBOA and successfully maintained good hemodynamic stability during the laparotomy. He was discharged at postoperative day 17 without ischemic symptoms of peripheral organs. Prophylactic use of REBOA could be useful for intra–abdominal bleeding caused by endogenous diseases like SAA as well as severe trauma. Also, we should keep in mind SAA rupture in patients in shock with liver cirrhosis and portal hypertension. 要旨: 肝硬変に伴う門脈圧亢進が成因と考えられた内因性脾動脈瘤破裂の開腹止血術に際して，予防的に大動脈内バルーン遮断（resuscitative endovascular balloon occlusion of the aorta: REBOA）を用いて良好な循環動態を保ち得た症例を経験したので報告する。症例は，非アルコール性脂肪肝炎，肝硬変，門脈圧亢進症，食道静脈瘤，高度肥満の既往がある46歳の男性で，左側腹部痛を主訴としショック状態で搬送された。食道静脈瘤の破裂による消化管出血も疑われたが，病歴・身体所見・腹部超音波検査から腹腔内出血を第1に疑い，造影CT所見から脾動脈瘤の破裂による腹腔内出血の診断とした。開腹止血術の方針となり，予防的にREBOAを挿入後に脾臓摘出術を施行した。術中は安定した循環動態が得られた。末梢臓器の明らかな虚血症状はみられず，術後17日に独歩退院した。予防的REBOAは重症腹部・骨盤外傷の止血術における有効性が示されているが，内因性疾患による腹腔内出血に対する緊急開腹止血術においても，有効であると考えられる。また，肝硬変・門脈圧亢進症患者のショックでは，脾動脈瘤の破裂による腹腔内出血を鑑別に置くべきである。